2005
DOI: 10.1080/09548980500289973
|View full text |Cite
|
Sign up to set email alerts
|

Critical band masking in optic flow

Abstract: Visual processing has been widely investigated with narrow band stimuli at low contrasts. We used a masking paradigm to examine how visual sensitivity under these conditions compares with the perception of the direction of heading in real scenes (i.e., with dynamic natural images at high contrasts). We first confirmed and extended previous studies showing biases in the amplitude distribution for spatial frequency, temporal frequency, speed and direction in dynamic natural movies. We then measured contrast thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 101 publications
(160 reference statements)
0
16
0
Order By: Relevance
“…van Hateren & van der Schaaf, 1998) because they contained a greater variation of image content, including more people, interior images and man-made objects and fewer close-up images of natural foliage which were considered a more representative sample of everyday natural scenes. Elsewhere, single frames from many different commercial movies (including cartoons) have been examined and it has been shown that with an assumed luminance gamma value of 2 for the camera, their amplitude spectra are comparable to those of images from calibrated databases (Bex, Dakin, & Mareschal, 2005). If there are residual concerns about the use of this class of image rather than those obtained in rural settings, US individuals 12 years and older spend an average of 4.7 hours per day watching television (not including time spent observing computer images and movies, U.S. Census Bureau 2008) and so this class of image represents a significant proportion of natural (or at least ‘everyday’) retinal input.…”
Section: Methodsmentioning
confidence: 99%
“…van Hateren & van der Schaaf, 1998) because they contained a greater variation of image content, including more people, interior images and man-made objects and fewer close-up images of natural foliage which were considered a more representative sample of everyday natural scenes. Elsewhere, single frames from many different commercial movies (including cartoons) have been examined and it has been shown that with an assumed luminance gamma value of 2 for the camera, their amplitude spectra are comparable to those of images from calibrated databases (Bex, Dakin, & Mareschal, 2005). If there are residual concerns about the use of this class of image rather than those obtained in rural settings, US individuals 12 years and older spend an average of 4.7 hours per day watching television (not including time spent observing computer images and movies, U.S. Census Bureau 2008) and so this class of image represents a significant proportion of natural (or at least ‘everyday’) retinal input.…”
Section: Methodsmentioning
confidence: 99%
“…Its amplitude spectrum falls approximately as "1/5" for 5 d A, which is a characteristic of the temporal amplitude spectrum dynamic natural images (Atick, 1992;Bex, Dakin, & Mareschal, 2005;Billock, de Guzman, & Scott Kelso, 2001;Dong & Atick, 1995;van Hateren, 1997).…”
Section: A Signal Transmission Model Of Contrast Constancymentioning
confidence: 98%
“…Natural images contain a great variety of visual features such as spatial frequency, luminance, contrast, orientation, texture, color, or optic flow signals (Dong and Atick, 1995; Billock et al, 2001; Bex and Makous, 2002; Betsch et al, 2004; Bex et al, 2005, 2007, 2009). Optically induced image modifications such as astigmatic blur and distortions of spectacles alter multiple features of the natural world; and the visual system adapts to them (Adams et al, 2001; Sawides et al, 2010; Yehezkel et al, 2010; Vinas et al, 2012, 2013).…”
Section: Introductionmentioning
confidence: 99%